2023
DOI: 10.3390/electronics12132900
|View full text |Cite
|
Sign up to set email alerts
|

A Customized ECA-CRNN Model for Emotion Recognition Based on EEG Signals

Abstract: Electroencephalogram (EEG) signals are electrical signals generated by changes in brain potential. As a significant physiological signal, EEG signals have been applied in various fields, including emotion recognition. However, current deep learning methods based on EEG signals for emotion recognition lack consideration of important aspects and comprehensive analysis of feature extraction interactions. In this paper, we propose a novel model named ECA-CRNN for emotion recognition using EEG signals. Our model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Understanding and achieving desirable results in the field of emotion recognition remains a challenging task, presenting opportunities for further innovation and investigation. Although previous studies [7,28,30,32,34,38] have demonstrated satisfactory results, there are still critical issues yet to be addressed, such as robustness, generalizability, and handling of intra-subject variability and observation variations. To address these gaps, this work aims to develop a robust and flexible pipeline for emotion recognition that can be applied to real-world data, while also mitigating the impact of these challenges.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding and achieving desirable results in the field of emotion recognition remains a challenging task, presenting opportunities for further innovation and investigation. Although previous studies [7,28,30,32,34,38] have demonstrated satisfactory results, there are still critical issues yet to be addressed, such as robustness, generalizability, and handling of intra-subject variability and observation variations. To address these gaps, this work aims to develop a robust and flexible pipeline for emotion recognition that can be applied to real-world data, while also mitigating the impact of these challenges.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Prior studies have demonstrated a strong correlation between EEG emotions and EEG frequencies [24,25]. Typically, EEG frequency features are extracted by mapping the EEG signals to Theta (4-7 Hz), Alpha (8-13 Hz), Beta (14-29 Hz), Gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), and other frequency bands [26]. Dimensionality reduction and classification are also essential stages in the emotion classification pipeline [27].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…ECA (Efficient Channel Attention) [29] is a channel attention module widely used in visual perception modeling. It can perform channel feature enhancement on multichannel input features [46], and the size of the feature map will not be altered after enhancement using ECA. Hence, the ECA module can enhance the model without increasing the complexity of modeling benefits.…”
Section: Eca Blockmentioning
confidence: 99%
“…Accordingly, researchers use EEG in various domains that involve neural engineering, neurosciences, and biomedical sciences (e.g., brain–computer interfaces, BCIs) [ 5 , 6 ]. EEG signal plays a crucial role in several EEG-based research and application areas such as clinical applications for epilepsy [ 7 ], depression [ 8 , 9 ], the effective monitoring of emotion [ 10 ], mental stress [ 11 , 12 , 13 ], and sinogram [ 14 ].…”
Section: Introductionmentioning
confidence: 99%